Spin-glass model predicts metastable brain states that diminish in anesthesia - Hudetz, Anthony G.; Humphries, Colin J.; Binder, Jeffrey R. (Frontiers in Systems Neuroscience, 2014)
Patterns of resting state connectivity change dynamically and may represent modes of cognitive information processing. The diversity of connectivity patterns (global brain states) reflects the information capacity of the brain and determines the state of consciousness. In this work, computer simulation was used to explore the repertoire of global brain states as a function of cortical activation level. We implemented a modified spin glass model to describe UP/DOWN state transitions of neuronal populations at a mesoscopic scale based on resting state BOLD fMRI data. Resting state fMRI was recorded in 20 participants and mapped to 10,000 cortical regions defined on a group-aligned cortical surface map. Each region represented the population activity of a ~20mm2 area of the cortex. Cross-correlation matrices of the mapped BOLD time courses of the set of regions were calculated and averaged across subjects. In the model, each cortical region was allowed to interact with the 16 other regions that had the highest pair-wise correlation values. All regions stochastically transitioned between UP and DOWN states under the net influence of their 16 pairs. The probability of local state transitions was controlled by a single parameter T corresponding to the level of global cortical activation. To estimate the number of distinct global states, first we ran 10,000 simulations at T=0. Simulations were started from random configurations that converged to one of several distinct patterns. Using hierarchical clustering, at 99% similarity, close to 300 distinct states were found. At intermediate T, metastable state configurations were formed suggesting critical behavior with a sharp increase in the number of metastable states at an optimal T. Both reduced activation (anesthesia, sleep) and increased activation (hyper-activation) moved the system away from equilibrium, presumably incompatible with conscious mentation. During equilibrium, the diversity of large-scale brain sta